Implementasi Kebijakan Program Strategis Nasional pada PT. Waskita Karya - Febriansah, Yefri; Akbar, Bahrullah; Suwanda, Dadang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research examines the implementation of PT's National Strategic Program. Waskita Karya specializes in the construction of the Depok-Antasari toll road. The purpose of this research is to find out and analyze how PT. Waskita Karya as the implementing agency for the construction of the Depok-Antasari toll road implements the policy, knows and analyzes the supporting and inhibiting factors for implementing the policy, as well as the efforts made to overcome the factors inhibiting implementation. This research was designed using 4 indicator dimensions, namely: communication, resources, disposition and bureaucratic structure. The method used is qualitative-descriptive which produces descriptive data in the form of speech or writing and behavior that can be observed from people or subjects. The techniques used to collect data are: observation, interviews, documents and audio-visual material by testing the validity of the data through the triangulation method based on sources, methods and theories. The informants in this research are: Secretary to the Minister of State-Owned Enterprises, Independent Commissioner of PT. Waskita Karya, Operational Director of PT. Waskita Karya, as well as Nur Afni and Novis Radhyan as community users of the Depok-Antasari toll road. Based on the results of this research, it can be concluded that the obstacle to implementing the National Strategic Program policy in the construction of the Depok-Antasari toll road is land acquisition, which apart from consuming a lot of budget, also wastes time. The problem of land acquisition specifically occurs because there is a lot of overlapping land ownership in the community, so they have to wait for a court decision to determine who actually owns the land rights. Researchers suggest that time space needs to be given to the Land Registration Agency (BPN) to disseminate information to the public about land ownership simultaneously so as not to waste time in implementing policies.